PERSEPSI MASYARAKAT TERHADAP TRADISI RANDAI DI DESA KOTO GADANG KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Alex Trio Weldi; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Randai the Minang community theater tradition in which there are dance,music and dialogue ( acting ). The aim of this study was the first to find out aboutpublic perception Koto district of Tanjung Raya Tower Agam against Randai.Second to determine the factors that cause a lack of public interest in the Randai.In the discussion of this research used the theories related to the title of theresearch such as understanding social change and understanding Randai. Datawas collected through field work methods which include several aspects:observation, interviews, literature study, and documentation. To supplementedthis research, analyzed data on public perception Koto Tower. The data wereanalyzed using descriptive qualitative method that is an analysis that provides adetailed description is based on the fact that encountered in the field andpresented in the form of description and calculation of numbers , percentages andtables .This research was conducted in the village of Tanjung Raya Koto TowerAgam District of West Sumatra province. The results of field research found thatthe public perception of Randai say that Randai not change so that people are notinterested in watching it. This suggests that changes in society that led to a lack ofpublic interest in the Randai. It is caused by several factors, namely, educationand mindset that has been developed, their discontent and the influence of othercultures.Keywords : Perception, Randai, Interest